Synthesis of several polyethers derived from BINOL and their application in the asymmetric borane reduction of prochiral ketones. Issue 4 (28th February 2015) - Zhang, An-Lin; Yu, Zeng-da; Yang, Li-Wen; Yang, Nian-Fa
Graphical abstract